DISSEMINATION STRATEGIES FOR RESEARCH FINDINGS TO SUPPORT KNOWLEDGE-BASED COMMUNITY EMPOWERMENT - Khasanah, Uswatun; Purwoko, Purwoko; Abidin, Zaenal; Adibah, Ida Zahara (Tahta Media Grup, 2026)
This Community Service (PKM) activity aims to implement a strategy for disseminating research findings to support knowledge-based community empowerment, particularly in the field of Islamic education. The activity was conducted online via an interactive webinar featuring two speakers who presented on the application of deep learning in Islamic education and the nurturing of a Qur’anic generation through teaching and mentoring children. Participants in the activity consisted of students from the Master’s Program in Islamic Religious Education (S2 PAI) and the general public. The method used was a participatory approach based on digital dissemination, comprising the stages of preparation, implementation, evaluation, and follow-up. The results of the activity indicated an increase in participants’ understanding of the presented material as well as a high level of satisfaction with its implementation. This was evidenced by the dominance of participants’ responses in the “good” and “very good” categories. Furthermore, this activity encouraged participants to implement the research findings in their teaching practices and community service activities within their respective environments. Thus, online-based dissemination of research results has proven effective in enhancing scientific literacy and supporting knowledge-based community empowerment. It is hoped that this activity will serve as a model for sustainable community service in the development of adaptive and contextual Islamic education.